Subacute Staphylococcus epidermidis Bacterial Endocarditis Complicated by Mitral-Aortic Intervalvular Fibrosa Pseudoaneurysm - Diane Elegino-Steffens; Amy Stratton; Jone Geimer-Flanders (Case Reports in Cardiology)
The patient is a 75-year-old man with a history significant for hypertension and congestive heart failure who underwent a bioprosthetic aortic valve replacement secondary to acute onset of aortic insufficiency. Cultures of the native valve were positive for Staphylococcus epidermidis sensitive to nafcillin and intravenous cefazolin was initiated. On postoperative day 24, he developed acute decompensated heart failure. A transesophageal echocardiogram demonstrated a structurally abnormal mitral valve with severe regurgitation, anterior and posterior leaflet vegetations, and scallop prolapse. There was also evidence of a mitral-aortic intervalvular fibrosa pseudoaneurysm (P-MAIF) with systolic expansion and flow within the aneurysm. Antibiotic treatment was changed from cefazolin to vancomycin for presumed development of methicillin-resistant Staphylococcus. He subsequently underwent a bioprosthetic mitral valve replacement and has restoration of health without sequella. This case highlights the development of a P-MAIF as a rare complication of both aortic or mitral valve replacement and infective endocarditis.